Impact of socio-demographic factors on Filipino consumers' level of vulnerability to false or misleading advertising - Abaloyan, Roxelle Joy O.; Ballais, Carlle Joseph A.; Busa, Alfonso B. Jr
At present, there is not much literature that studies the relationship between consumers' socio-demographic profiles and their level of vulnerability to false/misleading advertisements. Deceptive advertising is quite common in Philippine markets and is proving to be quite harmful to consumers. Thus, to raise awareness and possibly be of aid in addressing the issue, this study was conducted in an attempt to give an explanation as to what causes consumers to fall prey to these deceptive practices in advertising. The researchers selected 165 Filipino consumers from three selected locales within Region VIII to answer a survey questionnaire that measured their level of vulnerability to false or misleading advertising. Statistical and descriptive methods were employed to determine if there is a relationship between their socio-demographic profiles and their test results. A major finding of this study was there is a significant relationship between consumers' Sex, Gender, Age, Educational Attainment, Occupation, and Monthly Income and their level of vulnerability to false or misleading advertising. Moreover, it was discovered that the socio-demographic factors have a simultaneous or collective effect on the consumers' level of vulnerability to false or misleading advertising.